PENGARUH MODEL PEMBELAJARAN PBL MELALUI MEDIA VIDEO DALAM MENINGKATKAN PEMAHAMAN PEMBELAJARAN PPKN KELAS IV DI SD NEGERI BRINGIN 02 - Vina Indriana Rukmana; Fajar Ardina Manzilatul Rochmah; Muhammad Tasun; Susilo Tri Widodo; wulanauliaazizah@mail.unnes.ac.id (STKIP Subang, 2023)
The learning model really determines the learning outcomes of the students themselves. by needing to use a learning model that is appropriate and appropriate to the material to be taught. The aim of the research is to determine the improvement in PPKN learning outcomes for class IV SD Negeri Bringin 02 with the model Problem Based Learning assisted by video media. The subjects of this research were 22 students who met the requirements to be the research sample. Data collection was carried out in two stages, namely test and non-test. Non-tests are carried out by interviews with teachers and observations to see students' abilities in learning. To test by doing pretest before teaching the material and posttest after obtaining learning materials. The average pretest score was 51.82 and posttest 75.64 from 22 students, with an increase of 23.82. It was concluded that by implementing there was an influence of the Problem Based Learning model assisted by video media in increasing understanding of PPKN learning for class IV SD Negeri Bringin 02.